Forholdet mellem teologi og religionsvidenskab - Theissen, Gerd (Religionsvidenskabeligt Tidsskrift, 2004)
Theology and the Study of Religion answer distinct questions: Theology is committed to the truth of a concrete religion, but lacks universality. The Study of Religion deals with all religions, but brackets off questions of truth. For the time being, they both are incomplete because all academic studies must combine universality and truth. They both need one another. An outline shows how in general the Study of Religion may help Theology to a better understanding of its task - especially by explaining the theological contrast "revelation vs. religion" as a typical phenomenon of a "secondary religion" which originated by criticism of primary religions.